PENGEMBANGAN e-LKPD BERORIENTASI STEAM-PjBL UNTUK MENGOPTIMALKAN KREATIVITAS SISWA SMA KELAS XI PADA MATERI STOIKIOMETRI - Sekar Nanda Agustina; M. Rusdi; Febbry Romundza (PT. Hasba Edukasi Mandiri, 2025)
An interactive learning media based on e-LKPD can foster students’ creativity and learning interest, especially when presented with a simple and engaging design. Stoichiometry is one of the chemistry topics that involves abstract concepts. Therefore, the implementation of the STEAM-PjBL approach can help students connect concepts and theories with real-life contexts, making the learning process more relevant and meaningful. This study aims to identify the development process, usage procedures, feasibility of the media according to material and instructional design experts, teachers’ evaluations, and students’ responses toward the STEAM-PjBL-oriented e-LKPD developed for the stoichiometry topic. The development of the STEAM-PjBL-oriented e-LKPD employed the Lee & Owens development model. The research instruments included interview guidelines and questionnaires. The data analysis techniques used were qualitative and quantitative data analysis. The results of this study show that the material expert and instructional design expert assessments fall into the “satisfactory” category. Furthermore, the teachers’ evaluation obtained an average score of 4.9, categorized as “highly feasible,” and students gave positive responses during the small-group trial with a percentage score of 89.06%, categorized as “excellent.”